French laughter : literary humour from Diderot to Tournier - Redfern, W. D. (Oxford University Press, 2008)
The culmination of a lifetime's fascination with humour, Walter Redfern's book treats major French writers from the 18th to the 20th centuries as humorists, including Diderot, Rousseau, Sade Huysmans, Flaubert, Beckett, and Tournier. He considers irony hyperbole, wordplay, jokes, dialogue, humour as philosophical speculation, and plagiarism.